Governing bodies of global food organizations are lacking in gender and geographic diversity - Tanaka, Sonja; Parker, Alex (CGIAR GENDER Impact Platform, 2022)
"Key messages - More than 7 in 10 board seats (247/350) of organizations active in global food systems are held by nationals of high-income countries. This means that 70 percent of board seats represent just 16 percent of the global population. - Only 2 percent of board seats (7/351) are occupied by women from low-income countries, revealing huge disparities in the gender and geography of positions of power in global food systems organizations. - While organizations must be doing more to advance gender equality, there are positive shifts in the data. The proportion of women board chairs has increased - yet at just over one-third (16/45), this is still a far cry from gender parity. "